Analisis Strategi Pembelajaran Dalam Penanaman Edupreneurship Bagi Mahasiswa - Fira Nisa Rahmawati; Subiyantoro Subiyantoro (Universitas Hamzanwadi, 2022)
This study aims to explain the implementation of edupreneurship in the Islamic Religious Education study program at UIN Sunan Kalijaga, and how the learning strategy is. This study uses qualitative research with a focus on examining learning strategies in entrepreneurship courses in Islamic education in the Islamic Religious Education study program FITK UIN Sunan Kalijaga. In this study, researchers used source triangulation and data collection techniques. The participants who were sampled in this study used a purposive sampling technique with the research subjects being PAI students at the master's level of UIN Sunan Kalijaga who took the Entrepreneurship course in Islamic Education. The results showed that Sunan Kalijaga State Islamic University is one of the universities that has included entrepreneurship in its curriculum. One of them is at the Faculty of Tarbiyah and Teacher Training. This is the realization of the existence of entrepreneurship courses in several study programs, one of which is the PAI study program with the name of the course being entrepreneurship in Islamic education. The learning system, its application adheres to the subject matter that has been listed in the RPS which is then realized and integrated into other sciences which will be realized with a reputable journal article writing product. In addition, there are other variations of assignments, namely in the form of webinar assignments with predetermined themes. The strategy used in the learning uses the Inquiry learning strategy, Problem Based Learning and Project Based Learning